An overfilling indicator for wet overflow ball mills. (September 2016) - Shi, Fengnian
Highlights: An overfilling indicator for wet overflow discharge ball mills. Mathematical descriptions of volume-based slurry residence time in ball mills. 121 sets of plant survey data used to establish the slurry residence time patterns. The residence time thresholds as the overfilling indicator defined from the database. Abstract: The lack of constraints in ball mill capacity in the published ball mill models may result in unrealistic predictions of mill throughput. This paper presents an overfilling indicator for wet overflow discharge ball mills. The overfilling indicator is based on the slurry residence time in a given mill and given operational conditions. Mathematical descriptions of the method to estimate the volume-based residence time of slurry are presented. A database consisting of 121 sets of industrial overflow ball mill surveys worldwide was used to establish the pattern of the slurry residence time in the full scale operational overflow ball mills. According to the pattern, the residence time thresholds beyond which overfilling a ball mill is likely to occur were defined. For a ball mill with an internal diameter smaller than 5.9 m, the volume-based residence time threshold is set at 2 min; and for a ball mill larger than 5.9 m in diameter, the threshold is set at 1 min. In addition to being incorporated in ball mill models to warn of any unrealistic simulations, the overfilling indicator can also be utilised at ball mill operation sites to guide the mill throughput control and optimisation.